The immune checkpoint molecule, VTCN1/B7-H4, guides differentiation and suppresses proinflammatory responses and MHC class I expression in an embryonic stem cell-derived model of human trophoblast - Zhou, Jie; Tian, Yuchen; Qu, Ying; Williams, Madyson; Yuan, Ye; Karvas, Rowan M.; Sheridan, Megan A.; Schulz, Laura C.; Ezashi, Toshihiko; Roberts, Michael R.; Schust, Danny J. (Frontiers in Endocrinology, 2023)
The placenta acts as a protective barrier to pathogens and other harmful substances present in the maternal circulation throughout pregnancy. Disruption of placental development can lead to complications of pregnancy such as preeclampsia, intrauterine growth retardation and preterm birth. In previous work, we have shown that expression of the immune checkpoint regulator, B7-H4/VTCN1, is increased upon differentiation of human embryonic stem cells (hESC) to an in vitro model of primitive trophoblast (TB), that VTCN1/B7-H4 is expressed in first trimester but not term human placenta and that primitive trophoblast may be uniquely susceptible to certain pathogens. Here we report on the role of VTCN1 in trophoblast lineage development and anti-viral responses and the effects of changes in these processes on major histocompatibility complex (MHC) class I expression and peripheral NK cell phenotypes.